Induced Brain Plasticity after a Facilitation Programme for Autobiographical Memory in Multiple Sclerosis: A Preliminary Study. (18th October 2012) - Ernst, Alexandra; Botzung, Anne; Gounot, Daniel; Sellal, François; Blanc, Frédéric; de Seze, Jerome; Manning, Liliann
Abstract : This preliminary study tackles the assessment and treatment of autobiographical memory (AbM) in relapsing-remitting multiple sclerosis (RR-MS) patients. Our aim was to investigate cerebral activation changes, following clinical improvement of AbM due to a cognitive training based on mental visual imagery (MVI). We assessed AbM using the Autobiographical Interview (AI) in eight patients and 15 controls. The latter subjects established normative data. The eight patients showed selective defective performance on the AI. Four patients were trained cognitively and underwent pre- and post-AI and fMRI. The remaining four patients took a second AI, at the same interval, but with no intervention in between. Results showed a significant improvement of AbM performance after the facilitation programme that could not be explained by learning effects since the AI scores remained stable between the two assessments in the second group of patients. As expected, AbM improvement was accompanied by an increased cerebral activity in posterior cerebral regions in post-facilitation fMRI examination. We interpret this activation changes in terms of reflecting the emphasis made on the role of MVI in memory retrieval through the facilitation programme. These preliminary significant clinical and neuroimaging changes suggest the beneficial effects of this technique to alleviate AbM retrieval deficit in MS patients.